ELISA study of oocyst-sporozoite transition in malaria vectors - Czeher C.; Labbo R.; Djibrilla A.; Here L.; Arzika I.; Duchemin J.B. (Parasite, 2006)
Intrinsic vector characteristics and environmental factors affect the sporogonic development of P. falciparum in Anopheles mosquitoes. We tested for the presence of the circumsporozoite protein, as a marker of the oocyst to sporozoite transition in naturally infected Anopheles gambiae s.l. and Anopheles funestus. Malaria vectors were collected in a village in the Sahel of Niger during the rainy and dry seasons. ELISA-CSP was carried out on abdomen and head/thorax portions from more than 2,000 samples. No significant difference was found in the overall rates of infection of An. gambiae s.l. (4.13%) and An. funestus (3.58%). Given the differences in duration of the two parasite stages, P. falciparum CSP antigen prevalence was nearly as high in the abdomen as in the head/thorax, and did not differ significantly between An. gambiae s.l. and An. funestus. These preliminary results suggest that development from oocysts to salivary gland sporozoites is similar in the two vectors. However, these developmental indices varied as a function of the season in which samples were collected, particularly for An. gambiae s.l. This simple method may be useful for field studies assessing the effect of environmental and genetic factors on parasite survival.